Gain Parameter Adjustment Methods Comparison of Controller for Autonomous Rehabilitation Device - Ikbal ESKI; Ahmet KIRNAP (International Journal of Applied Methods in Electronics and Computers, 2016)
PID controller design and comparison between two different gain parameter adjustment method for autonomous physical rehabilitation device is presented in this paper. This device will be capable of doing repeated therapeutic exercises of shoulder joint. That devices main objective   is reducing physiotherapist work load. The controllers tested with real angel values. Comparison of simulation results showed Ziegler_Nichols adjustment method has better performance than Matlab's auto-tune method.